Understanding Hunters-Wildlife-Spirits Relationships around Natural Saltlicks: Analysis of Mythical Narratives of Hunters’ Experience (2021)
The knowledge of the drivers of geophagy in human and animals has received a wide spread debate among scientists but yet to reach a conclusive understanding. The idea of hunters hiding around natural saltlicks (NSs) for hunting is not new and has been in existence for more than a decade, however, little is understood about hunters-wildlife-lick (HWL) relationships, perhaps in a spiritual context. This has consequently limited our understanding of the mystery behind NSs of which eco-tourists depend for game viewing. Recently, knowledge on the existence of spirits in human-animal affairs is considerably gaining attention in the scientific world. Experience of such phenomenon is scarce among the park protection staff of Old Oyo National Park (OONP), except for the well-experienced old-hunters (OHs) who also lack documentation. Understanding this may perhaps elicit the impulse behind wildlife geophagy. This study therefore focuses on the assessment of hunters‟ experience on the spiritual myth of wildlife around NSs of OONP. To investigate this, a combination of semi-structured interview and personal observation methods were used. Nine volunteered key-informants (from among OHs not < 65years of age) were purposively selected across different ranges of the park for interview using snow ball technique. The results indicate that the OHs‟ experience of NSs seem not to vary, but spiritually based. It appears that OHs encounter with spirits-cum-wildlife is real, from whom they acquire favour for bumper harvest, spiritual divination and medicinal knowledge. This is a confirmation that hunter-wildlife-spirits (HWSs) relationships is an integral part of our nature, of which detail understanding may offer us a whole lot of new possibilities into the cause(s) of geophagy.